Chemotherapy as a Remedy to Gynaecological Cancers: Challenges and Coping Patterns Among Young Women - Titilayo Omolekan; Gbemisola Bolanle Ogbeye; Risikat Idowu Fadare (RGUHS Journal of Nursing Sciences)
Cancer was the primary cause of death for approximately 10 million people worldwide in 2020 accounting for one in every six deaths. According to the estimates between 2007 and 2030 there would be 11.5 million cancer-related fatalities worldwide a 45 rise from the current 7.9 million instances. With around 1.3 million new cases identified each year and more than six million survivors globally gynaecological cancers are the most prevalent forms of malignancies in women. Thus it is clear that gynaecological cancers pose a serious threat to public health. Chemotherapy is one of the cancer treatment modalities the side effects of which might affect young womens sexuality and functional status. Treatment for gynaecological cancers can result in both physical and psychological side effects such as hormonal changes vaginal changes such as dryness discharge shortening scarring early menopause pelvic floor disorders lymphoedema infertility discomfort exhaustion anxiety problems with body image and a crisis of feminine identity. A number of coping mechanisms have been noted including battling spirit positive reinterpretation helplessnesshopelessness and nervous obsession. In order to improve consistency in psychosexual support after treatment nurses should be well-equipped to talk about sexuality with their patients. Young women are at a heightened risk of infertility due to the gonadal toxic therapy-induced decrease of ovarian function. Efforts must be increased to conduct research on the preservation of fertility and sexuality in young women living with gynaecological cancers while receiving chemotherapy.